Phylogenomics of Bony-Tongue Fishes (Osteoglossomorpha) Shed Light on the Craniofacial Evolution and Biogeography of the Weakly Electric Clade (Mormyridae). (18th January 2022) - Peterson, Rose D; Sullivan, John P; Hopkins, Carl D; Santaquiteria, Aintzane; Dillman, Casey B; Pirro, Stacy; Betancur-R, Ricardo; Arcila, Dahiana; Hughes, Lily C; Ortí, Guillermo
Abstract: Bonytongues (Osteoglossomorpha) constitute an ancient clade of teleost fishes distributed in freshwater habitats throughout the world. The group includes well-known species such as arowanas, featherbacks, pirarucus, and the weakly electric fishes in the family Mormyridae. Their disjunct distribution, extreme morphologies, and electrolocating capabilities (Gymnarchidae and Mormyridae) have attracted much scientific interest, but a comprehensive phylogenetic framework for comparative analysis is missing, especially for the species-rich family Mormyridae. Of particular interest are disparate craniofacial morphologies among mormyrids which might constitute an exceptional model system to study convergent evolution. We present a phylogenomic analysis based on 546 exons of 179 species (out of 260), 28 out of 29 genera, and all six families of extant bonytongues. Based on a recent reassessment of the fossil record of osteoglossomorphs, we inferred dates of divergence among transcontinental clades and the major groups. The estimated ages of divergence among extant taxa (e.g., Osteoglossomorpha, Osteoglossiformes, and Mormyroidea) are older than previous reports, but most of the divergence dates obtained for clades on separate continents are too young to be explained by simple vicariance hypotheses. Biogeographic analysis of mormyrids indicates that their high species diversity in the Congo Basin is a consequence of range reductions of previously widespread ancestors and that the highest diversity of craniofacial morphologies among mormyrids originated in this basin. Special emphasis on a taxon-rich representation for mormyrids revealed pervasive misalignment between our phylogenomic results and mormyrid taxonomy due to repeated instances of convergence for extreme craniofacial morphologies. Estimation of ancestral phenotypes revealed contingent evolution of snout elongation and unique projections from the lower jaw to form the distinctive Schnauzenorgan. Synthesis of comparative analyses suggests that the remarkable craniofacial morphologies of mormyrids evolved convergently due to niche partitioning, likely enabled by interactions between their exclusive morphological and electrosensory adaptations. [Africa; ancestral state estimation; diversity; exon capture; freshwater fishes; Phylogenomics.]